STUDI LAYANAN PENEMPATAN DAN PENYALURAN UNTUK PENGEMBANGAN BAKAT SISWA SMA NEGERI 1 SUNGAI AMBAWANG - Sya ban, Gusti; Wicaksono, Luhur; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aims to gain help devalopment of talent student SMA Negeri 1 Sungai Ambawang of service placement and distribution. The method of this research is descriptive with research survey. The population in this research are 224 student and the sample are 54 student. The data collecting techniques of this research are direct comunication, indirect communication. The data instrument of this research interview guide, questionnaires. The conclusionof this research is that the activity of service placement and distribution to devalopment talent student SMA Negeri 1 Sungai Ambawang is 60% categorized moderate that is you say service placement and distribution already do it so increase again.Keywords:Â Service Placement and Distribution, Devalopment of Talent